THE IMPACT OF THE COMPLEX FOOD ADDITIVES ON THE GLANDULAR APPARATUS OF THE RAT’S DUODENAL MUCOSA - Bilash, V.P.; Grygorenko, A.S.; Yeroshenko G.А.; Shevchenko, K.V.; Lysachenko, O.D.; Zviaholska, I.M.; Tymoshenko, Yu.V.; Khilinska, T.V. (World of Medicine and Biology, 2021)
The effect of a complex of food additives of monosodium glutamate, sodium nitrite and Ponceau 4R on the state of the crypt of the mucosa of the duodenum of rats in the early stages of the experiment leads to a decrease in mean morphometric values of crypt body components, which subsequently leads to disorders of microcirculation in blood vessels, the development of hypoxia and the occurrence of an inflammatory reaction. As a result, increasing dystrophic changes in the cells of the epithelium of the intestinal glands develop, which is manifested by a decrease in the average values of the quantitative indicator of the cellular composition of the epithelium of the crypts. Further, as a result of compensatory-restorative reactions, complete recovery does not occur, which is confirmed by a decrease in the mean values of the metric values of the crypt body with decreasing epithelial cell height, against a decrease in epithelial cell composition and local immunity during the experiment.